2020
DOI: 10.1080/23311975.2020.1785105
|View full text |Cite
|
Sign up to set email alerts
|

Control and accountability in supply chain management: Evidence from a South African metropolitan municipality

Abstract: Accountability requires supply chain management (SCM) public officials to account for, report on, explain and justify activities, and accept responsibility for municipal financial expenditure outcomes. Regardless of having SCM systems in place, efficiency in terms of procuring, tendering and sourcing goods and services in South African municipalities remains problematic. A key contributory factor to regressions in local government audit outcomes is the constant failure to develop, implement and monitor effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…On the other hand, organizational theory describes that the empowerment is to delegate the authority to another person within the organization to perform any specific job activity (Mohajan, 2018). As per Sibanda et al, (2020) societal psychological theory describes that empowerment is the core cause behind the employee working and around working situation and he also elaborated six different related points like "potency, motivation, independence, values, relevancy and joy of life". It is as well as relevant to the employee inside growth, confidence, self-understanding and development (Khalid, et al, 2019).…”
Section: Employee Empowermentmentioning
confidence: 99%
“…On the other hand, organizational theory describes that the empowerment is to delegate the authority to another person within the organization to perform any specific job activity (Mohajan, 2018). As per Sibanda et al, (2020) societal psychological theory describes that empowerment is the core cause behind the employee working and around working situation and he also elaborated six different related points like "potency, motivation, independence, values, relevancy and joy of life". It is as well as relevant to the employee inside growth, confidence, self-understanding and development (Khalid, et al, 2019).…”
Section: Employee Empowermentmentioning
confidence: 99%
“…The implementation of these financial management goals can be analysed to evaluate their actualisation. Sibanda, Zindi and Maramura (2020) stated that the evaluation of the financial management goals involves an analysis of how effectively the financial resources have been managed to achieve the optimal goals of the municipality. The analysis of the actualisation of these goals in South Africa has revealed that there is financial mismanagement that can be described as unauthorised, irregular, fruitless and wasteful expenditure causing financial distress (Glasser & Wright 2020).…”
Section: Financial Mismanagement In South Africamentioning
confidence: 99%
“…Dlomo (2017) Furthermore, the Act describes expenditure that was not incurred in the manner prescribed by the legislation; this expenditure might have been incurred out of the budgetary guidelines, for instance, somewhere in the process that led to the expenditure, and the auditee did not comply with the applicable legislation that is stipulated in Municipal Finance Management Act 56 of 2003. Monkam (2014) stated that financial mismanagement in South Africa is a result of failures that are derived from poor supply chain management, performance reporting and risk management, whilst Sibanda et al (2020) found that one of the causes of financial mismanagement is inefficient internal control measures. Dlomo (2017) and Glasser and Wright (2020) also identified that municipalities in South Africa have poor internal control systems, and there is a need for the effective implementation of internal control measures to ensure that financial activities are completely accounted for and presented.…”
Section: Financial Mismanagement In South Africamentioning
confidence: 99%
“…Christopher (2015:957) identifies the lack of transparency and accountability measures in various South African municipalities as triggering inequalities and distracting municipal efforts of providing clean water and sanitation to the communities in need. In another study, Sibanda et al (2020) lament the lack of accountability measures in municipalities that affect the effective delivery of goods and services to satisfy human needs and wants as enshrined in the HRBA. The worrying trend of limited accountability in municipal development programmes acts against government efforts to curb the spread of COVID-19.…”
Section: Limited Accountability In Water Projectsmentioning
confidence: 99%